Menanggulangi Bullying: Tinjauan Faktor dan Upaya Pencegahan - Rayni, Inda Rahayu (Counseling AS SYAMIL: Jurnal Ilmiah Bimbingan Konseling Islam, 2024)
Negative actions that still occur in some schools are bullying, so that it can have an impact on the mental and emotional health of students. Research on bullying is able to provide solutions and solve existing problems against factors such as family factors, school environment, and even the social environment that often causes bullying. This study aims to provide solutions to overcome the occurrence of bullying in students at school. This study uses a descriptive method of qualitative analysis with a systematic literature review (SLR) approach by taking 21 scopus-based article documents that will be analyzed so as to produce data conclusions to answer problems related to this title. The results of this study show that bullying prevention efforts involve approaches that include developing social skills, increasing students' awareness of bullying behavior. In addition, it is important to pay attention to the factors that cause bullying to prevent bullying in schools and social environments. This research contributes significantly to tackling bullying as an effective instrument for bullying prevention.